The magical Narcissus: A study of the water-gazing motif in the Narcissus myth. - Nelson, Max. (University of Ottawa (Canada), 1997)
The originating context of myths (as interpretations of events, phenomena, or customs through narrative) can be discovered through a "structurist" approach in which the combination and function of traditional story elements or "motifs" are carefully examined and compared. By analyzing the motifs of the Narcissus myth in such a manner, the original context of the telling of the myth is to be ascertained. Scholars have interpreted the function of the original water-gazing Narcissus as arising from the superstition that one could lose one's soul in turbulent waters or that one could give oneself the evil-eye, but it makes most sense in terms of revelation. The originating context of the myth could then have been the importation of the rite of hydromancy from Egypt to Greece and Rome around 100 B.C. (perhaps by Bolus of Mendes or through the cult of Isis and Osiris), at which time the divinatory prescriptions were explained not rationally as means of hypnotizing a boy-medium, but as narrative elements in a mythological story. (Abstract shortened by UMI.)
Keywords: Literature, Classical.